2014
DOI: 10.4062/biomolther.2014.072
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Inhibits Cytokine-Stimulated Pancreatic Beta Cells by Blocking the ERK1/2 Pathway

Abstract: We show that silymarin, a polyphenolic flavonoid isolated from milk thistle (Silybum marianum), inhibits cytokine mixture (CM: TNF-α, IFN-γ, and IL-1β)-induced production of nitric oxide (NO) in the pancreatic beta cell line MIN6N8a. Immunostaining and Western blot analysis showed that silymarin inhibits iNOS gene expression. RT-PCR showed that silymarin inhibits iNOS gene expression in a dose-dependent manner. We also showed that silymarin inhibits extracellular signal-regulated protein kinase-1 and 2 (ERK1/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
1
9
0
1
Order By: Relevance
“…Macrophages play an important role in inflammation and in the pathogenesis of autoimmune diseases, and the inhibition of morphological and functional changes of macrophages by silymarin therefore indicated its potential to act as an anti-inflammatory agent. Our data, and those of others, have demonstrated that silymarin protected pancreatic beta cells from destruction induced by proinflammatory cytokines [ 25 , 28 ]. Proinflammatory cytokines are known to induce the expression of iNOS mRNA and the production of NO, resulting in beta cell death [ 29 , 30 ] An in vivo study using a rat model further showed that silymarin increased insulin gene expression and beta cell proliferation [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Macrophages play an important role in inflammation and in the pathogenesis of autoimmune diseases, and the inhibition of morphological and functional changes of macrophages by silymarin therefore indicated its potential to act as an anti-inflammatory agent. Our data, and those of others, have demonstrated that silymarin protected pancreatic beta cells from destruction induced by proinflammatory cytokines [ 25 , 28 ]. Proinflammatory cytokines are known to induce the expression of iNOS mRNA and the production of NO, resulting in beta cell death [ 29 , 30 ] An in vivo study using a rat model further showed that silymarin increased insulin gene expression and beta cell proliferation [ 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…RAW264.7 cells were treated with the indicated concentrations of silymarin in the presence of LPS (200 ng/ml) for 18 h. Culture supernatants were collected, and the accumulation of nitrite in culture supernatants was measured as an indicator of NO production in the medium, as previously described [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Silymarin is antiapoptotic in cytokine-induced MIN6 cell death. Treatment with 50 μ g/mL of silymarin reduced cytokine mixture-induced NF- κ B-activated NO production; the effect was mediated by ERK-1 and ERK-2 phosphorylation [ 114 ]. It has been reported that silymarin rescued pancreatic beta cell function in diabetic animals.…”
Section: Natural Bioactive Compounds For the Regulation Of Pancreamentioning
confidence: 99%
“…The anti-inflammatory effects of silymarin is mediated through the inhibition of NF-κB regulated gene products including COX-2 and Prostaglandin E2 (PGE2), as well as inflammatory cytokines 57 , through suppressing the degradation of Inhibitory kappa B (IκB) degradation, preventing both the translocation of NF-κB into the nucleus and the activation of gene transcription associated with inflammation 58 .…”
Section: Discussionmentioning
confidence: 99%